THE EFFECT OF COOPERATIVE LEARNING ENGINEERING MAKE A MATCH ON STUDENT ACHIEVEMENT IN LEARNING PAI STUDENTS OF SMPN 2 WEST TELUKJAMBE KARAWANG - Amirudin Amirudin; Iqbal Amar Muzaki (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Humans must understand that their education so far is not just mere formality. But more than that, education will largely determine the life of the nation and state, which are fostered from the elementary level. This study aims to assess the effect of Cooperative Learning taking a matching technique on student achievement. In this study, two groups were born. Namely, the Experiment group was given the Effect of Cooperative Learning Techniques Make Match on the learning outcomes of Grade VIII PAI students in SMPN 2 Telukjambe Barat and control groups with conventional learning. At the end of the study, a final test was conducted to see the learning outcomes of the PAI of the two samples. The results showed that applying the teaching model of cooperative learning type make a match was able to increase student achievement in class VIII SMPN 2 Telukjambe west and can change the way of thinking of students in the study the Islamic religious education to more fun and not dull, and can change the perspective of students in behaving better by showing good morals, courtesy and honesty.